Computer mediated parent-teacher communication = La comunicación entre padre-maestro mediada por computadora - Juniu, Susana (2009)
Parent-teacher communication is crucial to children's education. The literature reveals that parents' involvement in their children's education improves outcomes in areas such as learning, attendance, behavior, and graduation rates. Increased and meaningful communication between home and school is likely to enhance parent involvement and may consequently support students' learning. Schools are using various forms of technology to increaseschool/home communication, including voice mail, e-mail, school and classroom websites, and web access to individual student information such as attendance, grades, and student portfolios; however, this use is not consistent or widespread. This paper examines the most prevalent parent-teacher communication in a K-12 educational setting and explores various communication options to improve parent-teacher communication. The focus is to examine the communication needs between teacher and parents and the benefits of combining traditional synchronous and asynchronous communication with newer communication technologies to meet these needs.
La comunicación entre padres y maestros es crucial para la educación de los niños. La literatura revela que la participación de los padres en la educación de sus hijos mejora los resultados en áreas como el aprendizaje, asistencia, conducta, y en las tasas de graduación. Una comunicación efectiva entre la familia y la escuela aumenta la participación de los padres en la educación de sus niños y consecuentemente mejora el aprendizaje de los estudiantes. Las instituciones educativas están utilizando diversas formas de tecnología para incrementar la comunicación familia-escuela, entre ellas están el buzón de voz, el correo electrónico, páginas Web de las escuelas con acceso a la información personal de cada estudiante (asistencia, calificaciones, y actividades escolares). No obstante, este usono es consistente o masivo. Este ensayo examina las necesidades de comunicación entre los maestros y los padres y los beneficios de combinar comunicación tradicional, sincrónica (tiempo real) y asincrónica (con retraso), utilizando nuevas tecnologías de comunicación para satisfacer estas necesidades.
En Revista Actualidades Investigativas en Educación, Vol. 9, no. 3 (setiembre-diciembre 2009)
Descripción basada en el contenido visto el 06 de junio, 2025